The marketing promotion in the pharmacutical sector in Kosovo- case study - Asllani, Besa; Asllani, Gani; Grima, Simon (Edelweiss Applied Science and Technology, 2024)
The paper addresses the issues that have to do with the use of marketing and give a general overview for the pharmaceutical industry, the main marketing concepts, identify the importance of marketing in promoting sales of pharmacy companies, understand which strands are used to promote sales and satisfy the needs of consumers in terms of improving their health. In addition, the paper elaborates the development of the pharmaceutical sector in Kosovo, the competition between pharmaceutical producers and distributors, the strategies that firms use to promote products and services, increase of quality of medicines, price reduction and other issues. The objective of the paper is to explain how pharmaceutical marketing is carried out by focusing more on the communication and romotional techniques used, to give an overview of the functioning of this sector and to identify the importance of promotion in promoting sales. The methodology used is based on comparative analysis through the use of primary and secondary sources. For analysis purposes, a structured questionnaire was prepared for pharmaceutical products, which was distributed physically to the pharmaceutical workers. Scientific literature, local and international official reports and other relevant sources were also used. The results and findings of the research show that promotion has a significant impact on promoting sales.